KEBIJAKAN PENILAIAN KINERJA DOSEN DI PROGRAM PASCASARJANA UNIVERSITAS NEGERI JAKARTA - Dwi Deswary (Jurnal Manajemen Pendidikan, 2010)
This research aimed to know about the implementation of performance appraisal policy lecturer in the graduate program and the impact of policy implementation in the learning performance. data sources obtained from the director of PPs, Assistant Director I and II, Ka.Prodi, Sekprodi and lecturer at PPs UNJ. Data collected by observation, interview and documentation. Data is analyzed using descriptive approach. Research findings to inform you that the performance measurement needs to articulate the vision/mission, organizational goals, and objectives of the organization. Strategies for achieving goals through lecture attendance and dissemination of instruments to students. for the development of measurement systems, the leading commitee have prepared the lecturer performance assessment instruments and processing for field assessment instrument is being done to report the results to the lecturers. Whereas for use of performance measurement information needs to be followed up to make it more effective. In addition to improving performance is highly depend on individual commitment each lecturer.